Contemporary practice patterns of tyrosine kinase inhibitor use among older patients with chronic myeloid leukemia in the United States. (November 2021) - Shallis, Rory M.; Wang, Rong; Bewersdorf, Jan P.; Zeidan, Amer M.; Davidoff, Amy J.; Huntington, Scott F.; Podoltsev, Nikolai A.; Ma, Xiaomei
Introduction: The choice of BCR-ABL1 tyrosine kinase inhibitors (TKI) for the first line of therapy (LOT) for chronic-phase chronic myeloid leukemia (CML) is tailored to disease risk and patient characteristics like comorbidities, which become more prevalent with age. However, contemporary evaluations of frontline TKI choice and the factors associated with TKI switching in this specific patient population are lacking. Methods: We sought to describe TKI use in older patients (age: 66–99 years) with CML in the United States. Using the Surveillance, Epidemiology, and End Results–Medicare-linked database, we identified 810 older (median age: 75 years, interquartile range: 70–80 years) patients diagnosed during 2007–2015. Results: Imatinib was the most common frontline TKI (63.1%) throughout the study period, but its utilization as such decreased from 76% in 2010 to 47% in 2015. Most patients (65.3%) used only one TKI, but 12.5% of the 281 patients who switched from frontline TKI received ⩾4 LOT. Among the 167 patients switching from frontline imatinib, 18.6% eventually returned to imatinib with nearly all as the third LOT, supporting its favorable safety profile and indicating that the initial switch from imatinib might have been premature. Older patients within our cohort, white patients and those with greater comorbidity were less likely to switch from frontline TKI. Diagnosis year, geographic region, and surrogates for socioeconomic status and healthcare access had no impact on TKI switching. Conclusion: As expected, our findings highlight the frequent use of imatinib as the treatment option for older CML patients despite the availability of second-generation TKIs.